An endoscopic study on the prevalence of the accessory maxillary ostium in chronic sinusitis patients - Varadharajan, Ramesh; Sahithya, Swara; Venkatesan, Ranjitha; Gunasekaran, Agaman; Suresh, Sneha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic maxillary sinusitis is one of the common ENT problems. Accessory maxillary ostium (AMO) has been postulated in many publications to play a role in the development of chronic maxillary sinusitis. AMO is found in the medial wall of maxillary sinus and located in the lateral wall of the nose. It’s been frequently identified in the routine nasal endoscopy. The variations in the location of AMO have been evaluated by nasal endoscopy in live subjects or through cadaver dissections by many authors. This live study is conducted to identify the prevalence of AMO during nasal endoscopic evaluation of chronic sinusitis patients. Methods: 52 adult patients with symptoms of chronic sinusitis attending the ENT outpatient department were selected and subjected to X-ray of the paranasal sinuses and laboratory tests. Nasal endoscopy was done in all patients to identify the presence and location of the AMO and the results presented. Results: In the 52 patients studied the X-ray of the paranasal sinuses showed positive signs of sinusitis in 32 patients (61.5%). During nasal endoscopy in those 32 patients AMO was identified in 20 patients (62.5%). Conclusions: In patients presenting with symptoms of chronic sinusitis, apart from routine X-ray of the para nasal sinus, identification of the AMO during nasal endoscopy provides an additional evidence of obstruction of the natural ostia of the maxillary sinus. This will be valuable information to the surgeon who is contemplating on a surgical treatment to manage the chronic sinusitis.